Technical note: Measurements and data analysis of sediment–water oxygen flux using a new dual-optode eddy covariance instrument - M. Huettel; P. Berg; A. Merikhi (Biogeosciences, 2020)
Sediment–water oxygen fluxes are widely used as a proxy for organic carbon production and mineralization at the seafloor. In situ fluxes can be measured non-invasively with the aquatic eddy covariance technique, but a critical requirement is that the sensors of the instrument are able to correctly capture the high-frequency variations in dissolved oxygen concentration and vertical velocity. Even small changes in sensor characteristics during deployment as caused, e.g. by biofouling can result in erroneous flux data. Here we present a dual-optode eddy covariance instrument (2OEC) with two fast oxygen fibre sensors and document how erroneous flux interpretations and data loss can effectively be reduced by this hardware and a new data analysis approach. With deployments over a carbonate sandy sediment in the Florida Keys and comparison with parallel benthic advection chamber incubations, we demonstrate the improved data quality and data reliability facilitated by the instrument and associated data processing. Short-term changes in flux that are dubious in measurements with single oxygen sensor instruments can be confirmed or rejected with the 2OEC and in our deployments provided new insights into the temporal dynamics of benthic oxygen flux in permeable carbonate sands. Under steady conditions, representative benthic flux data can be generated with the 2OEC within a couple of hours, making this technique suitable for mapping sediment–water, intra-water column, or atmosphere–water fluxes.